The Helicopter Pilot—Swedish Hot-Area Policing From Above - Gerell, Manne; Kardell, Johan; Nilvall, Kim (Frontiers in Psychology, 2020)
Hot spot policing is an established concept that is proven to reduce crime. It is mostly done through foot patrol or car patrols. In the present study it is tested whether helicopters can produce a deterrent policing effect to reduce the amount of vehicle arsons in Sweden on larger hot areas. Sweden tends to have elevated levels of vehicle arsons in August, with about 20% of police districts responsible for 50% of the cases. The risk narrative revolves around youth congregating in public places in deprived neighborhoods to generate disturbances, and the disruption of the risk narrative tested here is based on providing deterrence through helicopter police presence. During six weeks in August and September of 2019 police helicopters patrolled four police districts in Sweden to attempt to prevent vehicle arsons. Our data comprise police reports of vehicle arson, and time stamped satellite data over the location for police helicopters. The evaluation considers whether there is an intention to treat effect from this project, in addition to whether there is an effect of actual helicopter presence. The study finds no significant effect of intention to treat, nor of actual dosage.